Hierarchical Factor Analysis and Factorial Invariance of the Chinese Overparenting Scale - Leung, Janet T. Y.; Shek, Daniel T. L. (Frontiers in Psychology, 2019)
Overparenting has become an emergent phenomenon where parents intrude into the lives and directions of their children and remove any anticipated obstacles that their children may encounter. This phenomenon develops rapidly across different ages, nations and cultures. This study examined the dimensionality of the Chinese Paternal/Maternal Overparenting Scales in 1,735 early adolescents (mean age = 12.63 ± .78 years; 47.4% were female) in Hong Kong. Confirmatory factor analyses indicated that an 8-factor model fitted the data well for both scales. The factors included close monitoring, intrusion of child’s life and direction, over-emphasis on child’s academic performance, frequent comparison of child’s achievement with others, overscheduling of child’s daily routine, anticipatory problem-solving, excessive affective response and excessive care. Hierarchical factor analyses showed that these factors could be subsumed under two second-order factors of “over-demandingness” and “over-responsiveness”, which provides support for the conceptual framework of parenting. Furthermore, the hierarchical factor models of the Chinese Paternal/Maternal Overparenting Scales were invariant in adolescent boys and girls; the scales and subscales showed good internal consistency. The present findings suggest that the Chinese Paternal/Maternal Overparenting Scales showed good factorial validity and reliability that can be used to assess overparenting objectively among early adolescents in the Chinese contexts.